Malignant hepatic tumour presenting at birth - Eckstein, Herbert B.; Marulyali, Keriman; Günalp, Altan (The Turkish Journal of Pediatrics, 1959)
A case of malignant hepatoma in a new-born baby is described; attempted partial hepatectomy was unsuccessful.We should like to thank Prof. Muharrem Köksal for the pathology report.